PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS KONSTRUKTIVISME YANG DILENGKAPI MIND MAP DALAM PEMBELAJARAN MATEMATIKA - Roza, Melia; Sefrinal, Sefrinal; Arif, Muhammad (STKIP Pesisir Selatan, 2020)
Learning resource is a material that can be utilized in support of teachers in the learning process, either directly or indirectly to improve the learning objectives. Learning resources that are usually used for teachers in the school including the Student Worksheet. The purpose of this peneltian is making mathematical constructivism-based learning device which features a mind folder on the material of the triangle and quadrilateral which is valid and practical. This research is research development by using the 4-D model of development which consists of define, design, develop, disseminate. In this phase, the needs analysis conducted define the analysis of curriculum, learner analysis, and analysis of materials-related problems in learning mathematics. On the design phase carried out the design of Constructivism-based student work sheet that comes mind folder on the triangular and quadrilateral meteri, then conducted a validation by experts. Phase test the practicalities do develop to a limited extent. The practicalities of data retrieved from sheet keterlaksanaan worksheet students, and practicalities of learners